PEMODELAN MEDIA ABOVE THE LINE BAGI TAMAN BELAJAR KITA DI JAKARTA BARAT - Fuad, Ahmad; Pratiwi, Ratih; Marwan, Rudi Heri; Purnamasari, Adhellia; Hardiatna, Anang; Ramadhan, Dzul Fadli Royan; Astriko, Feni; Wahyuningsih, Nining (Universitas Esa Unggul, 2021)
Our Learning Park was established because of the anxiety of the owner because of the learning conditions during this pandemic for elementary school children in the area around his house. For the upper middle class, where parents, especially mothers, can accompany their children to study. Unlike the lower middle class, in addition to having difficulty buying quotas for online schooling, they also have difficulty managing time to accompany their children to study, because mothers have to participate in making a living to help their husbands' income. With these conditions, many children are neglected and cannot take lessons from online schools. Because of these conditions, Taman Belajar Kita was established, which aims to help parents who do not have time and are unable to teach their children at home. Due to the poor conditions, the location for the teaching place is still considered not very feasible. Seeing these conditions, we carried out community service activities at the Taman Belajar Kita location in accordance with our field, the Visual Communication Design Study Program, namely by making murals that aim to beautify and increase the enthusiasm of students and educators in carrying out their activities. We made the mural for three days, by painting directly using paint on the outside of the room on the wall right on the stairs going up to the classroom, using a brush tool. Keywords: quota, online school, mural